The Opinion of Nipa palm farmer in WangWon Sub district, Kan Tang District, Trang Province - Phetchit, Jareporn (Journal of Science and Technology Songkhla Rajabhat University, 2020)
Study of Opinion the Nipa palm farmer in WangWon Sub-district, Kan Tang District, Trang Province. Data were collected by interviewing 100 farmers. Simple statistical methods were used to analyze data include mean, percentage, standard deviation T-test. 1) Farmers: The farmers are female. The average age was 45.70 years old (56%). They mostly graduated from secondary school. Have a household income of 11,463.23 baht a year. Planting Nipa plam for an average duration of 41.36 years. Use 4.87 rai/household. The popular species include KanDang and KanLay. The motivation to plant rambutan is inherited from ancestors. Farmers never received knowledge about Nipa plam planting. Never analyze nutrients in the soil. No fertilizer for Nipa plam. The sold in the form of fresh Nipa plam leaves. The sold to contractors. The selling frequency is 2 times / year, price 2,620.97 baht / rai / time. The average income is 5,241.93 baht / rai / year. Factors affecting the career in Nipa palm plantations, Economic (average 4.00), Social (average 4.18), Promotion and dissemination (average 3.83). Lack of support from the government. Suggestion: There are few rights to access the land and a lack of public relations to disseminate knowledge on planting from officials.